2023
DOI: 10.1136/bmjopen-2023-077685
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence and risk factors of neural tube defects in Ethiopia: a systematic review and meta-analysis

Neamin Tesfay,
Girmay Hailu,
Medhanye Habtetsion
et al.

Abstract: ObjectiveThis study aims to estimate the prevalence of neural tube defects (NTDs) and to identify potential risk factors in the Ethiopian context.Study designSystematic review and meta-analysis.Study participantsA total of 611 064 participants were included in the review obtained from 42 studies.MethodsPubMed (Medline), Embase and Cochrane Library databases in combination with other potential sources of literature were systematically searched, whereby studies conducted between January 2010 and December 2022 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 151 publications
(216 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, 77.9% women had low red blood cells folate concentration; hence, an increased risk of neural tube defect (NTD)-affected pregnancies [ 22 ]. A recent systematic review and meta-analysis of the literature showed that in Ethiopia the prevalence of all NTDs was 71 per 10,000 births, which is 2 times greater than the estimated prevalence in East Africa [ 23 ]. On the contrary, the recent food and nutrition survey report also shows that only 8% and 9% of reproductive age women in Ethiopia have iron and vitamin B12 deficiency [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 77.9% women had low red blood cells folate concentration; hence, an increased risk of neural tube defect (NTD)-affected pregnancies [ 22 ]. A recent systematic review and meta-analysis of the literature showed that in Ethiopia the prevalence of all NTDs was 71 per 10,000 births, which is 2 times greater than the estimated prevalence in East Africa [ 23 ]. On the contrary, the recent food and nutrition survey report also shows that only 8% and 9% of reproductive age women in Ethiopia have iron and vitamin B12 deficiency [ 24 ].…”
Section: Introductionmentioning
confidence: 99%